Lista de los peces marinos del Ecuador continental - Bearez, Philippe (Universidad de Costa Rica, 1996)
A new list of marine fishes from Ecuador is presented and 619 species are reported, both from the literature and from collected specimens. A new species and 14 new record s are included. When known, a local common name is given